Memetakan Target Pasar Teh Celup; Strategi Pemasaran Yang Efektif dan Efisien Untuk Konsumen Muda - Merichy Telaumbanua; Elmina Kita Ginting; Novita Sari Siboro (Student Research Journal, 2023)
Competition in various industrial fields is getting tougher, one of which is that competition in the beverage industry continues to develop. Facing the era of globalization, the business world must be able to improve company performance. In this way they can survive and compete. In accordance with changes in various economic fields, technical, political and market conditions are becoming increasingly evident. directly or indirectly Direct changes in the economic sector and current social conditions are also changing attitudes and consumer behavior. Product choice is the main marketing choice, not consumer choice. Just look at whether the brand or promotion is good and attractive, but product quality is also a choice. Competition in the tea industry has led to a decline in the performance of Tang Tea Bags in terms of customer satisfaction. Competition in various industrial fields is getting tougher, one of which is competition in the beverage industry continues to develop. Facing the era of globalization, the business world must be able to improve company performance. In this way they can survive and compete. In accordance with changes in various economic fields, technical, political and market conditions are becoming increasingly evident. directly or indirectly Direct changes in the economic sector and current social conditions are also changing attitudes and consumer behavior. Product choice is the main marketing choice, not consumer choice. Just look at whether the brand or promotion is good and attractive, but product quality is also a choice. Competition in the tea industry causes a decline in the performance of Tang Tea Bags in terms of customer satisfaction.